Dissecting aneurysm of the thoracic aorta: resección con by - pass temporario - Arias, José; Bogliaccini, Gustavo; Tchekmedyan, Vartan; Gastambide, Carmelo; Torres, Carlos; Gómez Haedo, Carlos; Su´arez, Raúl (Cirugía del Uruguay, 1980)
A dissecting aneurysm of the thoracic aorta resected under a temporary by - pass is presented. We befieve is the first case done in Uruguay. Sone treatment and pathologic aspects are pointed out. The patient had a good evolution.